2022
DOI: 10.3389/fchem.2022.962638
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Induced Polarization (AIP): Optical Rotation Amplification and Adjustment of Chiral Aggregates of Folding Oligomers and Polymers

Abstract: The phenomenon of aggregation-induced polarization (AIP) was observed showing optical rotation amplification and adjustment. The relationship between optical rotations of chiral aggregates of multilayered chiral folding oligomers and polymers with water% in THF (fw) has been established accordingly. New multilayered chiral oligomers were synthesized under the asymmetric catalytic systems established by our laboratory recently. These products were well-characterized by UV-vis, NMR, and MALDI-TOF spectra. Absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Our laboratory has recently proven that chiral aggregates can enhance asymmetric control and can even switch the stereo configuration of resulting chiral products ( Rouh et al, 2022 ; Tang et al, 2023 ). Chiral aggregates were directly confirmed by AIE, AIP (aggregation-induced polarization) ( Tang et al, 2022c ; Tang et al, 2022d ), and dynamic light scattering (DLS) experiments in THF-water and THF-ethanol co-solvents. Both stoichiometric and catalytic asymmetric reactions have been carried out successfully, defined as aggregation-induced asymmetric synthesis (AIAS) ( Tang et al, 2023 ) and aggregation-induced asymmetric catalysis (AIAC) ( Jin et al, 2022b ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Our laboratory has recently proven that chiral aggregates can enhance asymmetric control and can even switch the stereo configuration of resulting chiral products ( Rouh et al, 2022 ; Tang et al, 2023 ). Chiral aggregates were directly confirmed by AIE, AIP (aggregation-induced polarization) ( Tang et al, 2022c ; Tang et al, 2022d ), and dynamic light scattering (DLS) experiments in THF-water and THF-ethanol co-solvents. Both stoichiometric and catalytic asymmetric reactions have been carried out successfully, defined as aggregation-induced asymmetric synthesis (AIAS) ( Tang et al, 2023 ) and aggregation-induced asymmetric catalysis (AIAC) ( Jin et al, 2022b ).…”
Section: Resultsmentioning
confidence: 92%
“…In the past several years, our group has reported new multi-layer folding chirality of a series of molecules, including oligomers and polymers with structural flexibility, displaying physical properties on UV/Vis absorption, fluorescence, electrochemical performance, aggregation-induced emission (AIE) ( Wu et al, 2019 ; Wu et al, 2019 ; Liu et al, 2020 ; Wu et al, 2020 ; Wu et al, 2021a ; Jin et al, 2022a ; Tang et al, 2022a ; Tang et al, 2022b ; Wang et al, 2022 ), and aggregation-induced polarization (AIP) ( Tang et al, 2022c ; Tang et al, 2022d ). Among them are three-layer compounds ( Scheme 1 ), in which electron-rich ( Tang et al, 2022b ) and electron-deficient ( Jin et al, 2022a ) bridges showed distinct impacts on UV–vis absorption and fluorescence behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…This technique screened a series of BINOL and BINAP derivatives, and AIP phenomena were successfully observed in all cases. 21,22 Therefore, ligand 8a was selected as the representative for the AIP investigation. All measurements were nalized via Rudolph polarimeter (Rudolph Research Analytica APIV/2W) with samples prepared at the same concentration as c = 2 mg mL −1 under a 598 nm sodium lamp.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, our group investigated the relationship between the optical rotation of those chiral aggregates in multilayered chiral folding oligomers and polymers with increasing H 2 O percentage in the co-solvent system, and we characterize this phenomenon as aggregation-induced polarization (AIP). 28 However, little is known regarding the existence of this phenomenon in small chiral molecules. Herein, we would like to report our preliminary results of this study.…”
Section: Introductionmentioning
confidence: 99%